Demographic characteristics and accessibility as determinants of use of library resources by students in two Federal Colleges of Agriculture in Ibadan, Oyo State, Nigeria (2020)
The paper examined demographic factors and accessibility as determinants of use of library resources by students of Federal College of Animal Health Production and Federal College of Agriculture and Technology, Ibadan, Oyo state, Nigeria. Descriptive survey research design with the aid of questionnaire was employed to elicit response from the respondents. Simple random sampling technique was used to select the sample size of this work. Data was analysed with the use of descriptive statistics facilitated by the Statistical Software for the Social Sciences (SPSS). Results were presented in frequencies, percentages, correlation and multiple regressions on tables. From the findings, library resources that were very readily available were indicated. The prominent challenges affecting the use of library resources as indicated by most of the respondents were highlighted. Recommendations were also made based on the findings.